(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The research aims to know and measure the role of lean marketing in its dimensions (reducing excessive marketing activities, reducing unnecessary operations, reducing waiting time, reducing unnecessary movements), in sustainable competitive advantage in its dimensions (quality, creativity, cost, technology). The main problem of the research is an important question (to what extent can agile marketing contribute to achieving sustainable competitive advantage?). The research was conducted in a number of Iraqi telecommunications companies represented by (Zain and Asiacell), and the size of the population was the employees working in the companies, which It amounted to (120) individuals, and a sample was selected from it, which, according to statistical treatment, amounted to (114) individuals, who were the respondents to the research questionnaire that was prepared for this purpose. The researcher relied on the descriptive analytical approach to complete this research, and to analyze the data, the statistical program (Spss.v.28) was used. One of the most prominent findings of the research is that there is an impact of agile marketing on sustainable competitive advantage